2011
DOI: 10.1021/ja204042f
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Partitioning and Transmembrane Insertion of Hydrophobic Peptides under Equilibrium Conditions

Abstract: Nascent transmembrane (TM) polypeptide segments are recognized and inserted into the lipid bilayer by the cellular translocon machinery. The recognition rules, described by a biological hydrophobicity scale, correlate strongly with physical hydrophobicity scales that describe the free energy of insertion of TM helices from water. However, the exact relationship between the physical and biological scales is unknown, because solubility problems limit our ability to measure experimentally the direct partitioning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
136
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(158 citation statements)
references
References 45 publications
(105 reference statements)
15
136
1
Order By: Relevance
“…A recent study showed this exceptional thermostability by using a helical polyleucine peptide inserted into synthetic lipid vesicles. No loss of helical structure was observed by CD over a temperature range between 45 and 85°C (22). Our CD data of the 5-HT 3 R are consistent with a folding model of the protein subunit in a lipid membrane depicted in Fig.…”
Section: -Ht 3 R Increases Conformationalsupporting
confidence: 89%
See 1 more Smart Citation
“…A recent study showed this exceptional thermostability by using a helical polyleucine peptide inserted into synthetic lipid vesicles. No loss of helical structure was observed by CD over a temperature range between 45 and 85°C (22). Our CD data of the 5-HT 3 R are consistent with a folding model of the protein subunit in a lipid membrane depicted in Fig.…”
Section: -Ht 3 R Increases Conformationalsupporting
confidence: 89%
“…This has resulted in the proposal of a two-stage mechanism (21): during membrane insertion the ␣-helices form first and subsequently assemble into compact functional transmembrane protein structures. Since then, this model has been further refined and extended by taking into consideration the intermediate insertion steps such as helical protein parts at the membrane interface eventually switching to a transmembrane structure, as well as membrane protein oligomerization within the lipid bilayer (17,18,22).…”
mentioning
confidence: 99%
“…Consistent with this hypothesis, Ulmschneider et al (54) have shown by microsecond scale molecular dynamics simulations that polyleucine transmembrane segments with eight or more leucines can insert spontaneously. Another possibility with the highly hydrophobic TM segment is that the protein can use either the YidC-only or the Sec pathway.…”
Section: Discussionmentioning
confidence: 76%
“…To the extent that the translocon measures the thermodynamic preference for a sequence segment to insert in the bilayer or remain in an aqueous environment, 29 it makes sense that a lower free energy well would be required at high temperature to ensure the insertion decision is made. Theoretical calculations and experimental measurements indicate that the free energy of partitioning peptides into bilayers is relatively constant with temperature, 43,44 and hence higher temperatures should decrease the probability of insertion. This imperative may explain the general depletion of strongly polar residues that is observed.…”
Section: Discussionmentioning
confidence: 99%